1969
DOI: 10.1103/physrevlett.23.954
|View full text |Cite
|
Sign up to set email alerts
|

Local Thermodynamic Equilibrium Conditions in Superhigh-Pressure Helium Plasmas Produced by Laser Action

Abstract: Breakdown experiments in superhigh-pressure gases 1 irradiated by a focused Q-switched laser show a dependence of threshold electric field versus initial gas pressure in the rather large interval of 20 to 2000 atm. These curves present electric-field minima, which approximately agree with the values predicted by the wellknown theory of electron-impact ionization. In other kinds of experiments performed on laserproduced plasmas, 2 it has been shown that local thermodynamic equilibrium (LTE) conditions may be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1971
1971
1994
1994

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…De 151,5 à 2 040 atm les Tt tendent à se rapprocher de Tm2 et atteignent presque Tm2 à très haute pression. Le tableau IV résume l'ensemble des calculs ainsi que la figure 4. Ces résultats peuvent être comparés à ceux obtenus pour l'hélium [9] dans la même gamme de pression. A cette différence près que le minimum de claquage de l'hélium est beaucoup plus aplati [1] que dans le cas de l'argon pour un même accroissement de champ électrique de part et d'autre de ce minimum.…”
Section: Tableau IVunclassified
“…De 151,5 à 2 040 atm les Tt tendent à se rapprocher de Tm2 et atteignent presque Tm2 à très haute pression. Le tableau IV résume l'ensemble des calculs ainsi que la figure 4. Ces résultats peuvent être comparés à ceux obtenus pour l'hélium [9] dans la même gamme de pression. A cette différence près que le minimum de claquage de l'hélium est beaucoup plus aplati [1] que dans le cas de l'argon pour un même accroissement de champ électrique de part et d'autre de ce minimum.…”
Section: Tableau IVunclassified
“…No determination of kinetic temperatures was performed either. In general it is thought that LTE does not exist in high power pulsed plasmas, except at super high pressure [Rachman and Bassani, 1969]. Tonon, et al [1971] concluded that electron and ion kinetic temperatures are the same in a plasma produced by a giant laser pulse on a solid target.…”
mentioning
confidence: 99%